К вопросу о нормированности юго-западнорусского литературного языка XVI–XVII вв. (нa материалe употреблeния глaгольных форм в “Кaзаньи св. Кириллa” 1596 г.) - Целунова, Е. А. (Kalbotyra, 1988)
At the end of the 15th century in South-West Russia there appeared books written in the “prosta mova” (literary “simple” language), based on Ukrainian and Byelorussian dialects. One of the books of this kind is the “Kazanie of S. Kirill” (1596), translated from Polish by S. Zizany. The aim of the paper is to find out normative verbal forms in the “Kazanie” and to state the languages by which these forms where prompted to S. Zizany.